Pengembangan Media Pembelajaran Berbasis Video Menggunakan Aplikasi Tiktok pada Materi Akhlaq Berpakaian - Nurnaesih; Aspandi (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
This study aims to develop video-based learning media using the TikTok application for clothing morals material. This research refers to the development research method with the ADDIE model. Data collection techniques used learning expert validation tests and product trials on research subjects (class XI B students at MA Al-Hasyimiyah). Meanwhile, data analysis uses qualitative and quantitative analysis. The development results obtained a feasibility percentage of 95% (expert validation test) and 89.7% (group test questionnaire), so it was declared valid or suitable for use. Meanwhile, based on product implementation trials, it was found that it was effectively able to increase student learning outcomes by 12.4%. So this development study concludes that the clothing morals learning video product developed is valid and suitable for use in improving students' understanding and learning outcomes.